A Novel Reactive Current Injection (RCI) Control for Microgrid Protection with Inverter Based Distributed Generation (IBDG) - Oon, Kheng Heong; Tan, Chia Kwang; Bakar, Ab Halim Abu; Che, Hang Seng; Wong, Jorinda Yuh Ru (MDPI, 2019)
As the development of renewable distributed generations (DGs) is growing rapidly, the autonomous self-healing microgrid had emerged as an effective solution for integrating renewable DGs in the distribution networks. However, before the autonomous self-healing microgrid can be realized, one of the main issues that needs to be resolved is the ability to utilize the most cost-effective protection system—overcurrent relays—to achieve the goal. However, the overcurrent relay is insensitive to the limited fault current contributed by the inverter-based distributed generation (IBDG). Therefore, this paper will propose a novel inverter fault current control with a reactive current injection (RCI) that injects the correct fault current vector, albeit with a limited magnitude, for detection by the cost-effective directional overcurrent relay. This paper will also evaluate the performances of the different RCI controls in delivering an efficient self-healing microgrid protection based on a directional overcurrent relay. The proposed self-healing protection scheme is tested with both a simple distribution test network and also the IEEE 16 bus test system, considering random system parameters like variations in IBDG location, fault location, load capacity and load power factor. Moreover, the performance of the proposed inverter RCI control is also tested under changing weather conditions. © 2019 by the authors.